Aventinus - Språkbanken Text (University of Gothenburg, 2024)
You can find more information on the Aventinus project page.

Mer information hittas på Aventinus Projektsida.
Aventinus
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik